Preparation, Characterization and Biological Evaluations of New Bis (Azo-Acen) Ligands and Some of their Divalent TM Complexes - Mahdi, Saad Madlool (Iraqi Journal of Science, 2026)
A new azo-acetophenon ethylene-diamine ligands were synthesized through a multi-step procedure. The process initiated with the formation of an ACEN imine via that produced from the condensation of ethylene diamine and 4-aminoacetophenone, followed by diazotation of the ACEN amine group and subsequent coupling with components to form these two new ligands:- (1E,1'E)-N,N'-(ethane-1,2-diyl)bis(1-(4-((E)-(4,5-diphenyl-1H-imidazol-2-yl)diazenyl)phenyl)ethan-1-imine) L1 and3,3'-((1E,1'E)-(((1E,1'E)-(ethane-1,2-diylbis(azanylylidene))bis(ethan-1-yl-1-ylidene)) bis(4,1-phenylene))bis(diazene-2,1-diyl))bis(naphthalen-2-ol) H2L2. Comprehensive characterization of these ligands was conducted using FTIR, NMR, UV-visible, and Mass Spectroscopy complemented by C.H.N analysis. The corresponding PtL1 and pdL2 complexes were synthesized and identified with the previously mentioned techniques, meanwhile another technique as molar conductivity, magnetic susceptibility and XRD diffraction to deduce their morphology and geometry, from the biological side, three effective parameters were studied for these complexes (antibacterial ZOI, antioxidant and MCF7 cell line).